3D-Printed Tablets of Nifurtimox: In Vitro and In Vivo Anti-Trypanosoma cruzi Studies - Giselle R. Bedogni; Ana Luiza Lima; Idejan P. Gross; Tatiana Prata Menezes; Andre Talvani; Marcilio Cunha-Filho; Claudio J. Salomon (Pharmaceutics)
Background/Objectives: Chagas disease is a neglected tropical disease caused by infection with the parasite Trypanosoma cruzi. Benznidazole and nifurtimox are the only approved drugs for treating this condition, but their low aqueous solubility may lead to erratic bioavailability. This work aimed for the first time to formulate tablets of nifurtimox by hot melt extrusion coupled with 3D printing as a strategy to increase drug dissolution and the production of tablets with dosage on demand. Methods: Different pharmaceutical-grade polymers were evaluated through film casting, and those with promising nifurtimox amorphization capacity were further used to prepare filaments by hot melt extrusion. The printability of the obtained filaments was tested, and the polyvinyl alcohol filament was further used for printing tablets containing 120 and 60 mg of nifurtimox. Results: Three-dimensional tablets showed a remarkable improvement in the drug dissolution rate compared to commercial tablets and a dissolution efficiency 2.8 times higher. In vivo studies were carried out on Swiss mice. Parasitemia curves of nifurtimox printed tablets were significantly superior to the pure drug. Moreover, NFX 3D tablets provided a similar Trypanosoma cruzi reduction in plasmatic concentration to benznidazole, the gold-standard drug for acute-phase treatment of the Chagas disease. Conclusions: The findings of this work showed that hot melt extrusion coupled with 3D printing is a promising alternative for increasing nifurtimox biopharmaceutical properties and an attractive approach for personalized medicine.